Virtual study to investigate the detectability of breast abnormalities on 2D mammography and digital breast tomosynthesis - Kristina Tri Wigati; Hannah Manssens; Liesbeth Vancoillie; Cockmartin Lesley; Djarwani Soeharso Soejoko; Hilde Bosmans; Kristina Bliznakova (Indonesian Association of Physicists in Medicine (AIPM/AFISMI), 2018)
This paper describes the use of virtual clinical trial software, as developed and improved in the frame of the Horizon2020 MaXIMA project, to study particular aspects of 2D mammography and digital breast tomosynthesis. A voxel-based breast phantom with inserted mathematical models of an irregular mass and two microcalcifications was created. Image acquisition was simulated by using XRAYImagingSimulator, while image reconstruction was accomplished with FDKR software. Series of images were created for different angular ranges with an identical total dose. Detectability of the abnormalities was investigated using visual assessment and quantitative measurements. The results agree with other studies in literature studying the same aspects and therefore confirm the value of the new framework for other future applications.